Genetic Contribution of Emmer Wheat (Triticum dicoccon Schrank) to Heat Tolerance of Bread Wheat - Ullah, Smi; Bramley, Helen; Daetwyler, Hans; He, Sang; Mahmood, Tariq; Thistlethwaite, Rebecca; Trethowan, Richard (Frontiers in Plant Science, 2018)
Rising global temperatures cause substantial yield losses in many wheat growing environments. Emmer wheat (Triticum dicoccon Schrank), one of the first wheat species domesticated, carries significant variation for tolerance to abiotic stresses. This study identified new genetic variability for high-temperature tolerance in hexaploid progeny derived from crosses with emmer wheat. Eight hexaploid and 11 tetraploid parents were recombined in 43 backcross combinations using the hexaploid as the recurrent parent. A total of 537 emmer-based hexaploid lines were developed by producing approximately 10 double haploids on hexaploid like BC1F1 progeny and subsequent selection for hexaploid morphology. These materials and 17 commercial cultivars and hexaploid recurrent parents were evaluated under two times of sowing in the field, in 2014, 2015 and 2016. The materials were genotyped using a 90K SNP platform and these data were used to estimate the contribution of emmer wheat to the progeny. Significant phenotypic and genetic variation for key agronomical traits included grain yield, TKW and screening percentages was observed. Many of the emmer derived lines showed improved performance under heat stress (delayed sowing) compared with parents and commercial cultivars. Emmer derived lines were the highest yielding material in both sowing dates. The emmer wheat parent contributed between 1% and 44% of the genome of the derived lines. Emmer derived lines with superior kernel weight and yield generally had a greater genetic contribution from the emmer parent compared to those with lower trait values. The study showed that new genetic variation for key traits such as yield, kernel weight and screenings can be introduced to hexaploid wheat from emmer wheat. Therefore these genetic resources should be explored more systematically in breeding programs to stabilise grain yield and quality in future changing climates.